Pemanfaatan TIK Sebagai Media Pembelajaran dan Sumber Belajar oleh Guru TIK - Lestari, Isnania; Pratama, Meko Hendwi (Universitas Hamzanwadi, 2020)
Information and computer technology (ICT) is currently being used in all fields, including education. One of the uses of ICT in the field of education is for learning media and learning resources that can be used by teachers. This study aims to determine the extent to which the competence or ability of teachers, especially in ICT subjects, in utilizing ICT both as a medium of learning and a learning resource. The use of ICT is carried out to make it easier for teachers to implement the learning process. The research method used is descriptive with a survey form. The data collection tools used were questionnaires and interviews. The data analysis technique used is quantitative-descriptive to process questionnaire data and qualitative-descriptive to process interview data. Based on the data obtained, the use of ICT as a Learning Media and Learning Resources by Equivalent High School teachers in East Bunguran District, Natuna Regency is at a percentage above 80% with a high category. This shows that the teacher's ability to use ICT is very good. The learning media is majority often used are presentation processing applications and projectors. Meanwhile, the most widely used learning resource is the Internet.